Development of a pulsed magnetic field power supply for small size Betatron - Qi Liu; Jinhai Li; Haitao Wang; Yan Zhang; Haisheng Chen; Renbo Wang; Shumin Zhou (Nuclear Engineering and Technology)
In this paper, we present a new structure of capacitor-inductor discharge circuit and develop a pulsed magnetic field power supply for small size Betatron, addressing the urgent need for adjustable pulsed radiation frequencies. The proposed power supply employs insulated gate bipolar transistors (IGBTs) to control the discharge of the energy storage capacitor to the excitation winding, thus generating a pulsed current, which produces a pulsed magnetic field and accelerates the electrons. By adjusting the operating frequency of the IGBTs, the frequency of the pulsed current, and consequently the accelerator pulsed radiation frequency, can be regulated. The proposed design employs dual sustained paths, which are formed by the energy storage capacitor and the excitation winding, as well as a loss-compensation capacitor with the excitation winding. By adjusting the loss-compensation time, the problem of the pulsed current amplitude attenuation due to losses can be overcome, ensuring the stability of the pulsed magnetic field. Experimental results show that the power supply produces a pulsed current up to 220 A, which accelerates the electrons to 6.2 MeV, allowing the accelerator pulsed radiation frequency to be adjusted within a 333-Hz range. The proposed power supply makes small size Betatron suitable for a wide range of applications and provides technical knowledge for other types accelerators.